Réponses

2014-02-25T12:21:01+01:00
(x-2)(2x+5)=-10
⇔2x²+5x-4x-10=-10
⇔2x²+x-10+10=0
⇔2x²+x=0
⇔x(2x+1)=0 
⇔x=0 ou x=-1/2  (un produit est nul si l'un des facteurs est nul)

x-2(2x+5)=0
⇔x-4x-10=0
⇔-3x-10=
⇔3x=-10
⇔x=-10/3

(x-2)(2x+5)=0
⇔ x=2 ou x=-5/2
2014-02-25T12:49:26+01:00
Résoudre les équations suivantes :

(x - 2) (2x + 5) = -10
2x² + 5x - 4x - 10 = -10
2x² + x - 10 + 10 = 0
2x² + x = 0
x (2x + 1) = 0 
x = -1/2
ou
x = 0

x - 2 (2x + 5) = 0
x - 4x - 10 = 0
- 3x - 10 = 0
3x = -10
x = - 10/3

(x - 2) (2x + 5) = 0
x  = - 5/2
ou
x = 2